Disentangling the long‐term effects of disturbance on soil biogeochemistry in a wet tropical forest ecosystem. (15th January 2018) - Gutiérrez del Arroyo, Omar; Silver, Whendee L.
Abstract: Climate change is increasing the intensity of severe tropical storms and cyclones (also referred to as hurricanes or typhoons), with major implications for tropical forest structure and function. These changes in disturbance regime are likely to play an important role in regulating ecosystem carbon (C) and nutrient dynamics in tropical and subtropical forests. Canopy opening and debris deposition resulting from severe storms have complex and interacting effects on ecosystem biogeochemistry. Disentangling these complex effects will be critical to better understand the long‐term implications of climate change on ecosystem C and nutrient dynamics. In this study, we used a well‐replicated, long‐term (10 years) canopy and debris manipulation experiment in a wet tropical forest to determine the separate and combined effects of canopy opening and debris deposition on soil C and nutrients throughout the soil profile (1 m). Debris deposition alone resulted in higher soil C and N concentrations, both at the surface (0–10 cm) and at depth (50–80 cm). Concentrations of NaOH‐organic P also increased significantly in the debris deposition only treatment (20–90 cm depth), as did NaOH‐total P (20–50 cm depth). Canopy opening, both with and without debris deposition, significantly increased NaOH‐inorganic P concentrations from 70 to 90 cm depth. Soil iron concentrations were a strong predictor of both C and P patterns throughout the soil profile. Our results demonstrate that both surface‐ and subsoils have the potential to significantly increase C and nutrient storage a decade after the sudden deposition of disturbance‐related organic debris. Our results also show that these effects may be partially offset by rapid decomposition and decreases in litterfall associated with canopy opening. The significant effects of debris deposition on soil C and nutrient concentrations at depth (>50 cm), suggest that deep soils are more dynamic than previously believed, and can serve as sinks of C and nutrients derived from disturbance‐induced pulses of organic matter inputs. Abstract : Climate change is increasing the intensity of severe tropical storms and hurricanes. These changes in disturbance regime are likely to play an important role in regulating ecosystem carbon (C) and nutrient dynamics in tropical forests. Canopy opening and debris deposition resulting from severe storms have complex and interacting effects on soil biogeochemistry. Debris deposition only significantly increased soil C, N, and P concentrations, both at the surface (0–10 cm) and at depth (50–80 cm), even after a decade of ecosystem recovery. Our results demonstrate that both surface and subsoils have the potential to increase soil C and nutrient storage in response to the pulses of organic matter associated with the impact of severe tropical storms and hurricanes on tropical forests.